Pengembangan Video Animasi Kayla Berbicara Sebagai Media Dakwah Untuk Meningkatkan Perilaku Terpuji Siswa Sekolah Dasar - Ani Nur Aeni; Shabira Khairunnisa Pratidina; Ananda Awaliyah Rahmah; Irma Nurhalimah (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2022)
The commendable behavior of the current generation is being eroded by the flow of technology that tends to be modern. This study aims to improve the commendable behavior of elementary school students by motivating Kayla Talking Animation Video, which is applied as a da’wah medium. The data measured included the results of the assessments of grade 4-A and 4-B students at SDN Sukanegla. The data collection method used is the method of observation and interviews. Data were analyzed descriptively and qualitatively and the design used in this study was Design and Development (D&D). By giving questions before and after the product trial, Kayla Talking Animation. This method was carried out on 4th-grade students in the trial of the Kayla Talking Animation video product as a medium of da’wah, which discussed 4 commendable behaviors: fond of reading, unyielding, humble, and frugal. This material is taken from the elementary school curriculum in lesson 8 grade 4 semester 2. Based on the product validation assessment by the expert, the average overall rating indicator obtained a value of 4 with a very decent category. Based on the class 4 test results, the average score before and after the product trial, there was an increase of 27.54%, or 9.09. In addition, the difference in the average score after testing the product is 61.21. Thus, the Animated Video of Kayla Talking is effective enough to be used as a medium of da'wah in elementary schools.